Pharmacogenomics and Translational Simulations to Bridge Indications for an Anti‐Interferon‐α Receptor Antibody. Issue 6 (14th February 2013) - Wang, B; Higgs, B W; Chang, L; Vainshtein, I; Liu, Z; Streicher, K; Liang, M; White, W I; Yoo, S; Richman, L; Jallal, B; Roskos, L; et al.
<x xml:space="preserve">Abstract</x> A type I interferon (IFN) gene signature shared by systemic lupus erythematous (SLE) and systemic sclerosis (SSc) was used to evaluate an anti‐type I IFN‐α receptor (IFN‐αR) monoclonal antibody, MEDI‐546, in a phase I trial in SSc. MEDI‐546 suppressed IFN signature in blood and skin of SSc patients in a dose‐dependent manner. To bridge clinical indications to SLE, we developed a model incorporating (i) pharmacokinetics (PK) and pharmacodynamics (PD) in SSc patients, (ii) internalization kinetics of MEDI‐546/IFN‐αR complex, and (iii) the different IFN signatures between SSc and SLE. Simulations predicted that i.v. administration of MEDI‐546 at 300‐ or 1, 000‐mg monthly doses could suppress IFN signature in blood to levels of healthy subjects in 53 and 68% of SLE patients, respectively. An innovative approach utilizing a novel biomarker characterized the PD of MEDI‐546 by modeling and simulation and allowed rapid progression of MEDI‐546 from a phase I study in SSc to a randomized, multiple‐dose phase II trial. Clinical Pharmacology & Therapeutics (2013); 93 6, 483–492. doi:10.1038/clpt.2013.35